A cowboy to rely on [large type] - Kemerer, Jill (Kemerer, Jill. Wyoming ranchers romance., 2021)
"Still processing his grief, Jet Mayer is shocked to learn his late brother had a secret wife and child. Though he's neck-deep running his family's ranch, nothing will keep Jet from supporting Holly and little Clara. But Holly wants to follow her own path - even if Jet's the steadfast man she once wished for. Can they somehow reconcile their dreams to make a forever life together?" -- Back cover.